PENGARUH PENGARUH EDUKASI GIZI MENGGUNAKAN MEDIA AUDIO VISUAL (VIDEO) TERHADAP PENGETAHUAN DAN SIKAP GIZI SEIMBANGPADA SISWA KELAS V SEKOLAH DASAR SINT CAROLUS BENGKULU - Br H, Debora Tisa (UPPM Politeknik Kesehatan Kemenkes Ternate, Maluku Utara, Indonesia, 2020)
Media use can be said to be effective when communication with the media can also alter or influence one's behavior. The purpose of this research is to know the influence of nutritional education using audio Visual media (video) to the knowledge and attitude of balanced nutrition at Sint Carolus Elementary School Bengkulu. Design research of quasi experiments with pre-post with control group design. The research was conducted in 2019 at Sint Carolus Elementary School Bengkulu. The population of this study is all students of the V-grade Sint Carolus Elementary School Bengkulu. The samples used are V-grade students who meet inclusion and exclusion criteria. All samples are given pre and post questionnaires, then given educational video. The results of this study have a significant influence between the education of nutrition with knowledge (P = 0.000) and attitude (P = 0.022) so that there can be inferred there is influence of nutrition education using audio visual media (video) to knowledge and attitude of nutrition To Sint Carolus Elementary School Bengkulu.